Effectiveness Of The Role Of Manpower Planning On The Productivity Level Of PT ABM Investama Tbk (Case study: PT Cipta Kridatama and PT Cipta Krida Bahari Warehouse ) - Aisyah Lasahido; Alldila Nadhira Ayu Setyaning (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Currently PT ABM Investama is focusing on increasing company productivity, marked by the creation of a productivity dashboard to facilitate management in monitoring employee productivity levels. Productivity can be increased by making output effective and input efficient. This research discusses how to increase productivity, by making the existing manpower planning system more effective. This research is qualitative research with a focus on the case study type of research. The researcher chose to use a research method with the case study type because the researcher himself went directly into the company. In CKB there is a gap in manpower between planning and actual due to considerations to make labor costs more efficient than planned by increasing employee overtime, whereas in CK there is The manpower gap in planning and actual is due to consideration of the opportunity costs incurred if the human resources provided are less than required. The manpower system in ABM uses case studies for each business unit from 2 subsidiaries to find out how input can be made efficient from in terms of costs and number of workers with an effective manpower system so that it can influence the company's productivity level.